1913 Senior Year Book - San Jose State Normal School:::Creator:::; Roberts, Elizabeth:::Contributor:::
The annual yearbook included photographs and stories covering the school year's events, class members, student organizations, student clubs, student societies, faculty members, and sports. Earlier issues also included poetry and humorous stories and anecdotes.